Pengaruh Pengungkapan Emisi Karbon, Biaya Lingkungan, Kepemilikan Saham Publik dan Struktur Modal Terhadap Kinerja Keuangan Perusahaan - Yelsi Riska Yanti; Sofie (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to examine the effect of carbon emissions disclosure, environmental costs, public share ownership, and capital structure on financial performance. The population in this study consists of companies in the energy and transportation sectors listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The method used in selecting the research sample was purposive sampling. Based on the predetermined criteria, a total of 342 unbalanced samples were obtained in this study. This study uses panel data regression analysis techniques. The analysis is assisted by using Eviews 9 software. The results of the study indicate that carbon emissions disclosure, environmental costs, and capital structure do not affect financial performance. Meanwhile, public share ownership has a positive effect on company financial performance. It is hoped that this study can be beneficial for the government to pay more attention to the environmental impacts caused by company operational activities, as well as to monitor companies in fulfilling their responsibilities toward the surrounding environment. Additionally, it is hoped that this study can provide knowledge or information to investors in making decisions when considering investing in the company. Furthermore, it is hoped that this study can serve as a reference for future research.